2010
DOI: 10.1007/s00216-010-3680-1
|View full text |Cite
|
Sign up to set email alerts
|

Absolute quantification of superoxide dismutase (SOD) using species-specific isotope dilution analysis

Abstract: Here we report for the first time the use of species-specific isotope dilution mass spectrometry for the absolute quantification of a metalloprotein using nondenaturing gel electrophoresis laser ablation inductively coupled plasma mass spectrometry (GE-LA-ICP-MS). The concept utilises the intrinsic metals of the metalloprotein for labelling of the isotopically labelled spike ((65)Cu, (68)Zn SOD). The stability of the metal-protein complex under non-denaturing conditions during 1-D PAGE was confirmed and the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…Other studies report the same combination (gel electrophoresis with LA‐ICP‐MS) as for example the work conducted by Dietrich and collaborators, work performed on the absolute quantification of SOD using species‐specific isotope dilution analysis (Deitrich et al, ). Within this study a species‐specific isotopically enriched SOD was used as a tracer for the determination of this enzyme in bovine liver.…”
Section: Metals and The Livermentioning
confidence: 99%
“…Other studies report the same combination (gel electrophoresis with LA‐ICP‐MS) as for example the work conducted by Dietrich and collaborators, work performed on the absolute quantification of SOD using species‐specific isotope dilution analysis (Deitrich et al, ). Within this study a species‐specific isotopically enriched SOD was used as a tracer for the determination of this enzyme in bovine liver.…”
Section: Metals and The Livermentioning
confidence: 99%
“…Additionally, LA-ICP-IDMS can also correct for some common fractionation and matrix effects that cannot be controlled using other calibration procedures. So far, however, only a few investigations have assessed the analytical performance of IDMS in combination with GE-LA-ICP-MS [71,74,75].…”
Section: Quantification Strategiesmentioning
confidence: 99%
“…Deitrich et al [75] reported the use of an isotopically enriched 65 Cu, 68 Zn-superoxide dismutase (SOD) complex in an attempt to quantify natural SOD in a spiked liver extract subjected to nondenaturing 1D-PAGE. The stability of the isotopically enriched metal-protein complex was carefully investigated.…”
Section: Quantification Strategiesmentioning
confidence: 99%
“…This can be achieve by reducing the pH as in the case of TRF [9] or by adding chelating agent such as ethylendiamintetraacetate (EDTA) as the most successful way for SOD [10]. The released metals or the EDTA complexes of the metals have to be removed from the solution by dialysis or filtration with a centrifugal filter with a cut-off smaller than the protein investigated.…”
Section: Production Of Isotopically Labelled Metalloproteinsmentioning
confidence: 99%